Influência do método de preparação de catalisadores bifuncionais, Pt-Ni/HUSY, na isomerização do n-hexano - Yoshioka, Carlos Minoru Nascimento (2008)
Gasoline containing high amount of linear chain compounds have low octane number. However, this number can be increased when linear alkanes are subjected to isomerization, able to change linear chain compounds to ramificationcontaining alkanes. Such reactions require the use of bifunctional catalysts, containing acid and metal sites, which show high efficiency in the isomerization of linear chain paraffins. Most work in the literature involves the use of bifunctional catalysts with constant mass of metal and with high activation time of the catalyst, the so-called "Traditional Activation ". Therefore, the goal of this work is to study the influence of the method of preparation of bifunctional metallic catalysts through two methods of activation, in order to obtain a catalyst with well dispersed metallic particles. These catalysts had been reduced through the "Fast Activation" that consists in using high speed of heating in the process of reduction of cations. In this work, bifunctional and bimetallic catalysts supported in the FAU zeolitic structure containing constant molar content of Pt-Ni were prepared. The addition of these metals in the solid was accomplished through competitive ionic exchange, using solutions of these metals cations. Three series of metallic catalyst had been prepared, contaning 130, 230 and 280 µmol M/gcat. They have been characterized by temperature programmed of reduction (TPR), hydrogen chemisorption, transmission electronic microscopy (TEM), CO infrared spectroscopy and submitted to catalytic evaluation in the isomerization of n-hexane. From analysis of the results, it is possible to conclude that the fast activation process is more advantageous than the traditional one, then it avoids the migration of cations to small cavities of the zeolitic structure, minimizes the process of sintering of metallic particles and requires a much less time of activation. The insertion of a second metal (nickel) in the platinum bifunctional catalyst leads to getting solids with different properties from those that contain only platinum. Thus, it becomes possible to obtain bimetallic catalysts that are more active than the ones containing only one metal, even if it is noble metal.